2015
DOI: 10.1016/j.ygyno.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of expanded perioperative thromboprophylaxis in complex gynecologic surgery

Abstract: Objective To determine the effectiveness and safety of an expanded perioperative venous thromboembolism (VTE) prophylaxis strategy in women undergoing complex gynecologic surgery. Methods We performed a cohort study of 527 patients undergoing major surgery at a single institution over a thirty-month interval during which the gynecologic oncology service implemented an expanded approach to VTE prophylaxis. We compared rates of VTE pre- and post-intervention as well as bleeding and infectious complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…Using the conventional Caprini risk score groupings, 96.9% of gynecologic oncology patients are classified in the highest risk group with a score of ≥5. This finding is supported by two previous studies which found that >92% and >96% of patients operated on by a gynecologic oncologist were categorized in the highest Caprini risk groups (9, 10). For the Rogers score, 63.0% of patients are classified in the high-risk group with a score of ≥11.…”
Section: Commentsupporting
confidence: 85%
See 1 more Smart Citation
“…Using the conventional Caprini risk score groupings, 96.9% of gynecologic oncology patients are classified in the highest risk group with a score of ≥5. This finding is supported by two previous studies which found that >92% and >96% of patients operated on by a gynecologic oncologist were categorized in the highest Caprini risk groups (9, 10). For the Rogers score, 63.0% of patients are classified in the high-risk group with a score of ≥11.…”
Section: Commentsupporting
confidence: 85%
“…Both found that gynecologic oncology patients score high using the Caprini risk assessment model with >92% and >96% falling into the highest risk category, suggesting a limited ability to risk stratify as the vast majority of patients are categorized in a single stratum (9, 10). However, further examination into the possibility of risk stratification within this highest risk category has not been performed and the Rogers score has yet to be examined in a gynecologic oncology patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a score of 8 or higher had 2.1 times the odds of developing a venous thromboembolism within 30 days of surgery as those with a score of 5. An additional single institution prospective quality improvement study of 527 patients found that 96% of their patients with gynecologic cancers had a Caprini score in the highest group confirming the results of these two studies [17]. Although the American College of Chest Physicians recommends the Caprini score as a tool to risk stratify patients undergoing gynecologic oncology surgery, these data highlight challenges to its use in this population.…”
Section: Risk Assessmentmentioning
confidence: 66%
“…They found that the addition of preoperative pharmacologic prophylaxis to existing institutional practice significantly decreased the incidence of both deep vein thrombosis (1.3% to 0.2%) and pulmonary embolism (1.0% to 0.4%) without any increase in either blood transfusions or major bleeding events. A smaller similarly designed quality improvement project of 527 gynecologic oncology patients compared a pre-intervention protocol of mechanical prophylaxis and postoperative pharmacologic prophylaxis to a post-intervention protocol that added both preoperative pharmacologic prophylaxis for all patients and extended duration prophylaxis for patients with cancer [17]. They observed a decrease in 90-day venous thromboembolism incidence from 6.7% to 2.3% and similarly found no increase in major postoperative bleeding events or infectious complications.…”
Section: Pharmacologic Prophylaxis Strategiesmentioning
confidence: 99%
“…It is estimated that in Poland DVT is diagnosed in approximately 50,000 people per year, while 20,000 patients per year suffer from PE [1]. Pulmonary embolism leads to death in 30% of the patients, while a proper anticoagulation therapy reduces PE-related mortality to 2-8% [2,3].…”
Section: Introductionmentioning
confidence: 99%